2020
DOI: 10.1158/1535-7163.mct-19-1137
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Androgen Receptor and Glucocorticoid Receptor Antagonist CB-03-10 as Potential Treatment for Tumors that have Acquired GR-mediated Resistance to AR Blockade

Abstract: CB-03-10 (cortexolone 17a-valerate-21-propionate) is a synthetic steroidal compound derived from cortexolone (11-deoxycortisone), an intermediate in cortisol biosynthesis. Characterization of the activity of CB-03-10 and its main related compound CB-03-05 (cortexolone 17a-valerate) included in vitro binding to the androgen and glucocorticoid receptors (AR and GR), antagonism of AR and GR transcriptional activities, and screening for antitumor activity across a selected panel of human prostate and in triplenega… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Additionally, insight into the interactions between these hormone receptors is needed. While a small number of studies have reported on the crosstalk between the various hormone receptors [97][98][99][100], their mechanism of action is still largely unknown. Thus, further research regarding these hormonal receptors in TNBC could lead to a new effective treatment for some patients.…”
Section: Future Directionsmentioning
confidence: 99%
“…Additionally, insight into the interactions between these hormone receptors is needed. While a small number of studies have reported on the crosstalk between the various hormone receptors [97][98][99][100], their mechanism of action is still largely unknown. Thus, further research regarding these hormonal receptors in TNBC could lead to a new effective treatment for some patients.…”
Section: Future Directionsmentioning
confidence: 99%
“…Gefitinib ( 89 ), BEZ235 ( 110 ), RAD001 ( 124 ) or RU486 ( 131 ) were also reported to re-sensitize resistant cells to standard chemotherapy agents ( Supplementary Table 1 ). Interestingly, CUDC-907 ( 101 ), CB-03-10 ( 130 ) and MP470 ( 135 ), in addition to selective RTK inhibition, were found to inhibit HDAC6, AR and EGFR, respectively. These drugs caused cytotoxic effects in resistant cells ( Supplementary Table 1 ), indicating a possible benefit of targeting multiple pathways for management of resistant PCa.…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…Besides drug combination, a multiple target drug (a single drug acting on multiple targets) strategy has provided a promising opportunity for drug discovery and development. , Dervan’s group reported a pyrrole–imidazole polyamide ARE-1 showing both AR and GR transcription blockage and inhibition of ENZa-resistant mCRPC xenografts’ progression . In 2020, Rosette et al discovered a dual AR/GR antagonist, CB-03-10 , and its metabolite CB-03-05 , which inhibited the transcriptional activities of AR and GR in a dose-dependent manner (Figure ). Jorda et al found that a series of hydrocortisone ester compounds could repressively target AR and GR in PCa in vitro .…”
Section: Introductionmentioning
confidence: 99%